Discrete variational Lie group formulation of geometrically exact beam dynamics - Demoures, Francois; Gay-Balmaz, Francois; Leyendecker, Sigrid; Ober-Blöbaum, Sina; Ratiu, Tudor S.; Weinard, Yves (Numerische Mathematik, 2015)
The goal of this paper is to derive a structure preserving integrator for geometrically exact beam dynamics, by using a Lie group variational integrator. Both spatial and temporal discretization are implemented in a geometry preserving manner. The resulting scheme preserves both the discrete momentum maps and symplectic structures, and exhibits almost-perfect energy conservation. Comparisons with existing numerical schemes are provided and the convergence behavior is analyzed numerically. © 2014 Springer-Verlag Berlin Heidelber
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.ltd.discre_6